Pulmonary impairment independently determines mortality in critically ill patients with acute‐on‐chronic liver failure. (25th August 2022) - Schulz, Martin S.; Mengers, Jan; Gu, Wenyi; Drolz, Andreas; Ferstl, Philip G.; Amoros, Alex; Uschner, Frank E.; Ackermann, Nora; Guttenberg, Georg; Queck, Alexander; Brol, Maximilian J.; Graf, Christiana; et al.
Abstract: Background & Aims: In ACLF patients, an adequate risk stratification is essential, especially for liver transplant allocation, since ACLF is associated with high short‐term mortality. The CLIF‐C ACLF score is the best prognostic model to predict outcome in ACLF patients. While lung failure is generally regarded as signum malum in ICU care, this study aims to evaluate and quantify the role of pulmonary impairment on outcome in ACLF patients. Methods: In this retrospective study, 498 patients with liver cirrhosis and admission to IMC/ICU were included. ACLF was defined according to EASL‐CLIF criteria. Pulmonary impairment was classified into three groups: unimpaired ventilation, need for mechanical ventilation and defined pulmonary failure. These factors were analysed in different cohorts, including a propensity score‐matched ACLF cohort. Results: Mechanical ventilation and pulmonary failure were identified as independent risk factors for increased short‐term mortality. In matched ACLF patients, the presence of pulmonary failure showed the highest 28‐day mortality (83.7%), whereas mortality rates in ACLF with mechanical ventilation (67.3%) and ACLF without pulmonary impairment (38.8%) were considerably lower ( p  < .001). Especially in patients with pulmonary impairment, the CLIF‐C ACLF score showed poor predictive accuracy. Adjusting the CLIF‐C ACLF score for the grade of pulmonary impairment improved the prediction significantly. Conclusions: This study highlights that not only pulmonary failure but also mechanical ventilation is associated with worse prognosis in ACLF patients. The grade of pulmonary impairment should be considered in the risk assessment in ACLF patients. The new score may be useful in the selection of patients for liver transplantation.